Rural tourism and territorial development in Romania - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Rural tourism in Romania has significant potential. The Romanian effort to develop and promote tourism in the rural area has been completed by the support provided by the European Union funds. In this context, the objective of this paper is to highlight the territorial development of the rural tourism market after the Romania's accession to the European Union. The methodology used is based on the synthesis of information from articles and studies published in specialty journals, in Government documents as well as in other development strategies on tourism and rural space. The results reconfirm that the supply of tourist accommodation in rural areas has shown a general upward trend, despite a slight decline during the global financial crisis, and the investments in rural tourism activity have a great advantage, i.e. job creation and maintaining the local (rural) labour, revitalization of rural localities, mainly those from the less-favoured and remote rural areas.
Keywords: Q01; L83; R10; Z30; 330; rural development; rural tourism; competitiveness; regions; Romania